Improving Information-Sharing Across Law Enforcement: Why Can’t We Know? - Hollywood, John S.; Winkelman, Zev (RAND Corporation, 2023)
Law enforcement capabilities increasingly depend on records management systems and computer-aided dispatch systems, and there are increasing demands to share information across regional, state, and federal repositories. But there are limitations to existing information-sharing technology and policy. This report addresses both short-term and long-term approaches to overcoming those barriers.